Hiring preferences of special libraries in Makati - Dineros, Jennifer L.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
Among the resources that a library should spend on is a competitive staff. A competitive staff could maximize the potential of an institution whereas an uncompetitive staff could cause the elimination an established organization. It is necessary therefor to examine the hiring preferences of libraries.
This study focused on determining if there is a significant difference between the preferences of public and private special libraries in Makati in hiring personnel. It aimed to determine the qualifications that job applicants must possess in order be considered a candidate for an open position in public and private special libraries in Makati and to determine how public and private special libraries in Makati and to determine how public and private special libraries in Makati rank applicants that are qualified as candidates for an open position in terms of their preferences. It also aimed to compare and contrast the hiring preferences of both public and private special libraries in Makati. Data gathered through the survey research method from the seven public special libraries and seven private special libraries chosen from the population, which included all special libraries in Makati revealed that public and special libraries place high value on educational attainment, experience, course taken, specialization and language proficiency while private special libraries place high value on experience, educational attainment, course taken, computer proficiency and specialization.
The conclusion of the study were (1) the basic characteristics public and private special libraries in Makati look for in personnel are age (preferably between the age of 26 and 35 years), educational attainment (preferably with Bachelor's Degree), experience within the field of Library and Information Science (preferably 2-4 years), and course taken (preferably Library and Information Science, Information Technology or Law); (2) The qualifications used by public and private special libraries in ranking candidates for open positions are specialization (public special libraries prefer specialization in Information Technology while private special libraries prefer specialization in Law), language proficiency (preferably English and Filipino), computer proficiency (especially in Microsoft Office and internet searching) and other skills (preferably people skills); and (3) There is no significant difference between the hiring preferences of public and private special libraries in Makati except in the case of civil status. Recommendations included focusing on the special libraries found in other cities of Metro Manila or in other regions of the country and regarding the various categorizations and size of special libraries. It also included extending outside the realm of special libraries by dwelling on academic and public libraries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Employee selection -- Philippines -- Makati City; Special libraries -- Philippines -- Makati City; Vocational qualifications -- Philippines -- Makati City